Comprehensive approach for identification of functional FCGR2C alleles resulting in protein expression as a determinant for predicting predisposition to autoimmunity. Issue 2 (31st August 2021) - Lehmann, Dorit; Unterthurner, Sabine; Berg, Verena; Hock, Karin; Ponnuswamy, Padmapriya; Malisauskas, Mantas; Crowe, Brian A.; Erguener, Bekir; Bock, Christoph; Hather, Greg; Reipert, Birgit M.; Bilic, Ivan
Abstract: The balance of activating and inhibitory signals from the low affinity Fc gamma receptors modulates immune responses triggered by IgG antibody‐immune complexes. In homeostasis, this leads to antigen clearance, while in autoimmune diseases to unwanted immune response. Besides the activating receptors FcɣRIIa, FcɣRIIIa, and the inhibitory FcɣRIIb receptor, a third activating receptor, FcɣRIIc, was shown to be expressed on several immune cell types, however, only in the presence of a functional FCGR2C ‐ORF allele. FcɣRIIc expression is associated with autoimmune diseases such as idiopathic thrombocytopenic purpura, systemic lupus erythematosus or systemic sclerosis. Thus, the determination of the functional FCGR2C gene resulting in protein expression on immune cells becomes highly relevant, particularly in the context of unwanted immune responses through inadvertent FcɣRIIc activation by molecules targeting stimulation of the inhibitory receptor FcɣRIIb, currently pursued by several pharmaceutical companies. The high degree of homology within the FCGR2/3 gene cluster complicates development of an accurate method for identification of FcɣRIIc expression. Here we describe a comprehensive approach to characterize genetic status of the FCGR2C gene locus consisting of cDNA sequencing, SNaPshot genotyping and low‐coverage next‐generation sequencing. This might enable Mendelian randomization hypothesis testing across autoimmune diseases to personalize therapies and enhance treatment outcomes.